'When the music ends it stays in the brain': Agency and embodiment in young children's engagements with recorded music in preschool. (1st July 2020) - Gluschankof, Claudia
Listening to recorded music is ubiquitous both for adults and young children. In early educational settings, it is mainly used as background music to set up a certain atmosphere, and to design specific festivity environments and celebrations. Recorded musical pieces ‐ specifically instrumental ones, as the focus of the educational activities, because of their musical characteristics ‐ are seldom used. When they are used, musical pieces are considered isolated musical objects that children have to be taught to contemplate, understand and appreciate. This study presents a less-documented and reported type of young children's engagement with music: self-initiated and self-directed movement representations of recorded musical pieces documented by Sarit, a preschool teacher, for her educational purposes. The documents include videos of children's choreographies, Sarit's accounts, children's drawings and their explanations of them. These engagements give us opportunities to study agency in listening experiences and children's multimodal exploring, and ultimately embodied and visual representation of their musical understanding of the pieces. Children exercise agency in their engagement with the music, as they choose the music and what to do, with whom, with what and when, and in these doings, they change their preschool. In their choreographies, they embody their understanding of the music; and in their drawings, they share with us the whole process. Educators are invited to open their eyes and their ears, discovering children's multimodal engagements with recorded music.